The perceived impact of pre-service student teachers on the optimal learning environment of the students they teach and the teachers who mentor them - Walker, Adrian A (Kansas State University, 2014)
This study was designed to examine one component of impact within a High School Professional Development School (PDS) partnership. The purpose of this study was to explore the perceived impact of pre-service teachers on the students they teach and the cooperating teachers who mentor them. More specifically, this study was designed to explore the impact on the learning environment of high school students who were taught by pre-service teachers and the cooperating teachers who mentored them from the perspective of 8 pre-service teachers, 130 high school students, and 8 cooperating teachers. The theoretical framework for this study was based on the concept of an Optimal Learning Environment (National Research Council, 1999). The overarching question for this study was: In what ways do pre-service teachers impact the learning environment of the PDS in which they complete their final clinical experience? Survey and interview data were gathered from participants to explore the perceived impact of the pre-service teachers on the (a) learner centered learning environment, (b) assessment centered learning environment, and (c) knowledge centered learning environment of the high school students and cooperating mentor teachers. The data collected were focused on what the high school students, pre-service teachers and cooperating mentor teachers perceived based on their personal experiences and understanding. The results of this study indicated a perceived positive impact on the learner centered, assessment centered, and knowledge centered learning environments of the high school students and the cooperating mentor teachers from the perspectives of the high school students, pre-service teachers and cooperating mentor teachers. The researcher thus concluded that the pre-service teachers positively impacted the perceived Optimal Learning Environment of the PDS in which they completed their final clinical experience.
Keywords: Student teacher impact; Optimal learning environment; Perceptions of professional development school participants; Perceptions regarding student teachers; Higher Education (0745); Secondary Education (0533)